Pengaruh Stakeholder Pressure dan Shareholding Structure Terhadap Sustainability Report Quality - Darmawan, Muhammad Dzaky; Idawati, Wiwi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This research was conducted to examine and empirically determine the effect of stakeholder pressure as proxied by environmental-sensitive industry, consumer-proximity industry, investor-oriented industry, employee-oriented industry and creditor pressure, and shareholding structure as proxied by managerial shareholding and institusional shareholding on sustainability report quality. This research is quantitive research and uses research objects in the form of IDX80 companies on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample selection was carried out using purposive sampling technique and obtained 144 samples from 48 companies and tested using the STATA version 16 statistical application. This study found that investor-oriented industry, employee-oriented industry, managerial ownership and institutional ownership have no significant effect on sustainability report quality. Then environmental-sensitive industry, consumer-proximity industry and creditor pressure have a significant positive effect on sustainability report quality.